When Compact sets are -Closed - Ali, Haider Jebur; Dahham, Marwa Makki (Al-Nahrain Journal of Science, 2019)
This paper is devoted to introduce new concepts so called K( c)-space several various theorems about these concepts are provided In addition, further properties are studied such as the relationships between those concepts and other types of K( c)-spaces are investigated.